Edukasi Gizi Tanggap Darurat untuk Pencegahan Stunting Anak - Nurul Fathiyyah; Rakhmalia Imeldawati; Ainun Ganisia (Rena Cipta Mandiri, 2024)
Stunting remains a chronic nutritional problem requiring family-based promotive and preventive interventions, particularly in child feeding and beverage practices. This community service aimed to improve maternal nutrition literacy and cadre capacity regarding appropriate complementary feeding and limitation of sugar-sweetened beverages in Sawotratap Village, Gedangan, Sidoarjo. The program consisted of partner coordination, baseline survey, interactive education, demonstration of local food-based complementary menus, emergency menu simulation, pre-test and post-test evaluation, skills observation, and one-month monitoring. Participants included 47 mothers of children under five, 15 Posyandu cadres, and 8 village representatives. The mean knowledge score increased from 59.2 to 88.5, with an average gain of 29.3 points; 85% of participants improved by at least 25 points. During practice, 82% of mothers were able to arrange age-appropriate menus and 78% determined adequate animal protein portions. One-month monitoring indicated that 58% of families reduced sweetened beverage consumption and 61% of mothers provided animal protein at least four times per week. Participatory education combined with demonstrations may strengthen child feeding behavior and household nutrition preparedness.